FACTUAL INDETERMINACY IN INTERNATIONAL TAX LAW - B. Bogenschneider (BRICS Law Journal, 2016)
Legal indeterminacy comes in a variety of forms identified here as: (i) general legal indeterminacy; (ii) factual indeterminacy; and (iii) Mach/Feyerabend factual indeterminacy. The concept of general “legal indeterminacy” refers to problems in legal interpretation and has been extensively studied. “Factual indeterminacy” refers to the indeterminacy of facts as a matter of tax law when derived from separately indeterminate fields of law. “Mach/ Feyerabend factual indeterminacy” refers to fact words as derived from legal theory which provide the content for legal interpretation. The “facts” in tax law are not transcendent to law; in addition, the “fact” words of tax law cannot be simply imported from the field of economics. The incremental question of the origins of theory (as discussed by Karl Popper and Albert Einstein) is also analyzed here. The theory of tax law originates with “sympathy with experience” or “intellectual love” (tr. Einfühlung) of tax law by lawyers as reflected in the special heuristics and practices of the profession. Legal theory accordingly functions in similar fashion to scientific theory where a particular legal theory can be falsified (qua Popper) or understood in pluralistic terms by incorporating auxiliary ideas.